Indonesian language in Australian universities : strategies for a stronger future. - Hill, David T. (Office for Learning and Teaching, 2012)
This is the final report from a project that reviewed the dramatic decline in Indonesian language learning in Australian universities, The report presents a national strategy for Indonesian in Australian universities, outlining a series of recommendations to reverse the decline in Indonesian language studies in Australian universities, and to strengthen and reinvigorate Indonesian teaching and learning. The report is presented in four sections: an introduction, including a review of Australia's relationship with Indonesia; a description of the current state of Indonesian in Australian universities; a series of recommendations for component elements of a "National Indonesian Language in Universities Program" for implementation by government and universities; and a conclusion.